“Regularized” Exportation: Is it a Prerequisite to Enjoy the Benefit of Drawback? Regarding the Position Taken by Sunat and the Tax Court of Peru - Alva Falcón, César (2019)
The purpose of this article is to review the position taken by the Peruvian Customs and the Customs Chamber of the Tax Court of Peru related to what should be understood as the “regularization” of an export and the impact of that interpretation for the application and enjoyment of the customs regime of drawback. As a previous step, the authors discuss the conceptual part of the drawback regime in Peruvian legislation, making a brief account of its origins, background, supranational regulation, current scenario and the requirements that constitute it as a benefit for exporters. Finally, the authors analyze the position mentioned before.